Synthesis and Optical Resolution of 3,3,3′,3′-Tetramethyl-1,1′-spirobiindane-7,7′-diol - Zhou, Qiaoxia; Pan, Rihuang; Shan, Huanyu; Lin, Xufeng (Synthesis, 2019)
A novel chiral C2-symmetric spiro diol, 3,3,3′,3′-tetramethyl-1,1′-spirobiindane-7,7′-diol (TMSIOL), was conveniently prepared via practical seven-step route from Bisphenol A in 45.1% overall yield. l-Menthyl chloroformate is used as optical resolving agent for the separation of the two enantiomers of TMSIOL.
Keywords: asymmetric catalysis; chiral ligand; chiral diol; spirobiindane; resolution